Influence of deposition time on the supercapacitive performance of electrodeposited interconnected Co(OH)2 nanoflakes. (2022) - Patil, R.T.; Patil, A.S.; Patil, S.S.; Wadakar, N.B.; Patil, T.M.; Dhas, S.D.; Fulari, V.J.
Highlights: Co(OH)2 nanoflakes were developed on the stainless steel substrate by electrodeposition method. Prepared Co(OH)2 nanoflakes were used as electrode for supercapacitor. Co(OH)2 electrode exhibits 480F g −1 for 1 mA cm −1 . Abstract: In the electrodeposition process, the deposition time directly influences electrodes surface morphology and electrochemical performance. Cobalt hydroxide Co(OH)2 nanoflakes were produced potentiostatically on stainless steel at various deposition times (1, 2, 3, 4, 5 min) in this research work. The Co(OH)2 nanoflakes, could be a viable candidate for use as an electrode material in supercapacitor applications due to their innovative manufacturing and high capacitance. X-ray diffraction and field emission scanning electron microscopy were used to investigate the structural and morphological features of prepared nanoflakes. The supercapacitive performance was studied using cyclic voltammetry, galvanostatic charge–discharge, and electrochemical impedance spectroscopy techniques. The study reveals that deposition time and potential have an impact on the morphology of deposited material, and that morphology has an impact on electrochemical characteristics. In 1 M KOH, as prepared Co(OH)2 nanoflakes reveals a specific capacitance of 480F g −1 for 1 mAcm −1 . The Co(OH)2 electrode retained 79 % capacitance after 1000 cycles.